2015
DOI: 10.4236/ajps.2015.618275
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Nutrition, Its Regulation and Biotechnological Approaches to Improve Crop Productivity

Abstract: Nitrogen is the most important macronutrient needed for plant growth and development. The availability of nitrogen in the soil fluctuates greatly in both time and space. Crop plants, except leguminous plants, depend on supply of nitrogen as fertilizers. Large quantities of nitrogen fertilizers are applied to crop plants, but only 33% of it is utilized by the plant. Plants have developed efficient mechanisms to sense the varying levels of nitrogen forms and uptake them. They also have well developed mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 448 publications
(473 reference statements)
0
14
0
Order By: Relevance
“…During translocation and assimilation, inorganic nitrogen influx and efflux also takes place between the roots and the recirculating water. The reason of NO 3 efflux on its biochemical basis has not been fully discovered (Reddy and Ulaganathan, 2015;Segonzac et al, 2007). However, it has been known that the NO 3 efflux is mediated by NO 3 transporters such as NO 3 transporter 1.5 (NRT1.5) and nitrate excretion transporter 1 (NAXT1) of root plasma membrane (Reddy and Ulaganathan, 2015;Segonzac et al, 2007).…”
Section: Nitrogen Uptake By Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…During translocation and assimilation, inorganic nitrogen influx and efflux also takes place between the roots and the recirculating water. The reason of NO 3 efflux on its biochemical basis has not been fully discovered (Reddy and Ulaganathan, 2015;Segonzac et al, 2007). However, it has been known that the NO 3 efflux is mediated by NO 3 transporters such as NO 3 transporter 1.5 (NRT1.5) and nitrate excretion transporter 1 (NAXT1) of root plasma membrane (Reddy and Ulaganathan, 2015;Segonzac et al, 2007).…”
Section: Nitrogen Uptake By Plantsmentioning
confidence: 99%
“…The reason of NO 3 efflux on its biochemical basis has not been fully discovered (Reddy and Ulaganathan, 2015;Segonzac et al, 2007). However, it has been known that the NO 3 efflux is mediated by NO 3 transporters such as NO 3 transporter 1.5 (NRT1.5) and nitrate excretion transporter 1 (NAXT1) of root plasma membrane (Reddy and Ulaganathan, 2015;Segonzac et al, 2007). The NO 3 efflux is induced by stressed conditions such as medium acidification, defoliation, mechanical stress, transplant shock and pathogen attacks (Reddy and Ulaganathan, 2015;Segonzac et al, 2007).…”
Section: Nitrogen Uptake By Plantsmentioning
confidence: 99%
“…Glutamine synthetase also mediates ammonium assimilation into glutamine. Ammonium form of nitrogen is rapidly assimilated into organic nitrogen forms to avoid tissue toxicity, for review see [196]. Several other reviews have documented the genes and proteins regulating nitrogen use efficiency (NUE) in plants.…”
Section: Plant Tolerance To Nitrogen Deficiencymentioning
confidence: 99%
“…Several other reviews have documented the genes and proteins regulating nitrogen use efficiency (NUE) in plants. The reader is referred to excellent reviews by [177,196]. In addition, more than 50 QTLs for nitrogen use efficiency have been reported in plants, though few of them have been validated.…”
Section: Plant Tolerance To Nitrogen Deficiencymentioning
confidence: 99%
“…Moreover, studies have shown that plants have developed an advanced mechanism to deal with nitrogen deficiency, through uptake, transport, and assimilation of nitrogen under N-limited environment [11]. Furthermore, the plants only utilize 30% of the applied nitrogenous fertilizers, while the rest is either lost through leaching and or fixed in the soil [12].…”
Section: Introductionmentioning
confidence: 99%